Travel behavior changes during the COVID-19 pandemic in Japan: Analyzing the effects of risk perception and social influence on going-out self-restriction - Giancarlos Parady; Ayako Taniguchi; Kiyoshi Takami (Transportation Research Interdisciplinary Perspectives, 2020)
This article analyzes factors affecting travel behavior changes at the individual level in light of the COVID-19 pandemic in Japan, in the context of non-binding self-restriction requests. In particular, this study focuses on the effects of risk perception and social influence. A panel web-survey was conducted targeting residents of the Kanto Region, including the Tokyo Metropolis. In addition to describing the observed patterns in behavioral change, we modeled behavioral changes of four key, non-work-related activities: (i) grocery shopping, (ii) other types of shopping, (iii) eating out, and (iv) leisure. For eating-out and leisure the distinction was made between going alone or in groups. Based on the observed distributions of these activities, regression models of going-out frequency were estimated for shopping, while for eating-out and leisure, which showed considerably smaller frequencies, a discrete choice approach was used. Findings showed that as a measure of social influence, the perception of degree of self-restriction of others was associated with small reductions in shopping frequencies, and moderate yet non-negligible increases in going-out self-restriction probability for eating-out and leisure activities. Risk perception, measured as COVID-19 dread, was also associated with higher probabilities of going-out self-restriction for eating-out and leisure. These findings suggest that in the context of non-binding requests, soft measures such as campaigns to promote a reduction of non-essential travel might be more effective if they (i) properly convey the severity of the threat posed by COVID-19 as well as its coping mechanisms, and (ii) appeal to the group, rather than the individual, emphasizing the behavior (or at least the perception of behavior) of others.